Validating Nutrient Deficiencies in Abaca (Musa textilis Née var. Inosa) via Morpho-Physiological and Biochemical Analysis Under Field Conditions - Rosit, James Francienne J.; Armecin, Romel B. (Future Science / FSH-PH Publications, 2025)
This study was conducted in order to validate and compare the nutrient composition, morpho-physiological and biochemical properties of asymptomatic and symptomatic abaca in the field. This approach may provide insights on the possible association between disease infestation and nutrient deficiency symptoms observed in abaca. Three sampling sites were selected for sample collection; The National Abaca Research Center (NARC), Visayas State University, Baybay City, Leyte, Brgy. Basak, Maasin City and Brgy. Lonoy, Maasin City, Southern Leyte. Five sample plants for both asymptomatic and symptomatic plants were collected for data gathering. Field validation showed that asymptomatic showed better leaf morphology than symptomatic abaca plants. Furthermore, asymptomatic abaca plants have higher chlorophyll a and b content than symptomatic plants. Nitrogen, phosphorus, and potassium content in asymptomatic abaca plants were higher than symptomatic plants. Nitrogen content was higher in soils from asymptomatic abaca plants while phosphorus and potassium were very high on soils from symptomatic abaca plants. Despite the very high phosphorus and potassium content in symptomatic soils, abaca plants exhibited clear signs of nutrient deficiency, suggesting that excessive P and K may interfere with the availability or uptake of other essential nutrients, such as magnesium, calcium, or micronutrients like zinc and iron resulting to the occurrence of nutrient deficiency symptoms in the abaca plants.